PRE - OPERATIVE RECOVERY IN ACL REPAIR AND RECONSTRUCTION - Mihai Constantinescu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2019)
This article is designed to support and require a preoperative recovery program in knee ligaments when scheduled surgery is performed.